Leidynema bestium sp. n. (Oxyuridomorpha: Thelastomatidae) an intestinal parasite of blaberid cockroaches from Yaroslavl Zoo, Russia - Spiridonov, Sergei E.; Kiselev, Sergei M. (Zootaxa, 2022)
A new species of thelastomatid Leidynema bestium sp. n. is described from the hind gut lumen of the cockroaches Diploptera punctata (Eschscholtz, 1922) and Elliptorhina chopardi (Lefeuvre, 1966). The new species is characterized by a combination of morphological features: presence of lateral alae in both sexes with posterior margin of alae in females not ending in the shape of a spike; longitudinal striation of the anteriormost annuli in males; four male genital papillae, equatorial position of vulva. In the cladogram inferred from analysis of D2–D3 segment of LSU rDNA L. bestium sp. n. demonstrates a position independent of the Leidynema species with known sequences of this taxonomic marker near the basal node for this genus.